Intestinal microbiota in patients with nonalcoholic fatty liver disease12. Issue 1 (14th May 2013) - Mouzaki, Marialena; Comelli, Elena M.; Arendt, Bianca M.; Bonengel, Julia; Fung, Scott K.; Fischer, Sandra E.; McGilvray, Ian D.; Allard, Johane P.
Abstract Despite evidence that the intestinal microbiota (IM) is involved in the pathogenesis of obesity, the IM composition of patients with nonalcoholic fatty liver disease (NAFLD) has not been well characterized. This prospective, cross‐sectional study was aimed at identifying differences in IM between adults with biopsy‐proven NAFLD (simple steatosis [SS] or nonalcoholic steatohepatitis [NASH]) and living liver donors as healthy controls (HC). Fifty subjects were included: 11 SS, 22 NASH, and 17 HC. One stool sample was collected from each participant. Quantitative real‐time polymerase chain reaction was used to measure total bacterial counts, Bacteroides/Prevotella (herein referred to as Bacteroidetes), Clostridium leptum, C. coccoides, bifidobacteria, Escherichia coli and Archaea in stool. Clinical and laboratory data, food records, and activity logs were collected. Patients with NASH had a lower percentage of Bacteroidetes (Bacteroidetes to total bacteria counts) compared to both SS and HC (P = 0.006) and higher fecal C. coccoides compared to those with SS (P = 0.04). There were no differences in the remaining microorganisms. As body mass index (BMI) and dietary fat intake differed between the groups (P < 0.05), we performed linear regression adjusting for these variables. The difference in C. coccoides was no longer significant after adjusting for BMI and fat intake. However, there continued to be a significant association between the presence of NASH and lower percentage Bacteroidetes even after adjusting for these variables (P = 0.002; 95% confidence interval = −0.06 to −0.02). Conclusion: There is an inverse and diet‐/BMI‐independent association between the presence of NASH and percentage Bacteroidetes in the stool, suggesting that the IM may play a role in the development of NAFLD. (HEPATOLOGY 2013 )